(untitled) (International Journal of Nursing Education, 2021)
Background: Stress is very common among students belonging to the healthcare domain. They are more exposed to stressful factors than the rest of the student community. It is of extreme importance to evaluate the level of stress among the students of the bachelor’s degree in Nursing, as well as to know the factors involved. Method: Study quantitative, descriptive scope, and cross-sectional. The academic stress level was measured on 332 students from different semesters of the bachelor’s degree in Nursing, through of the short version of the “About Stress in University Students questionnaire”. Conclusion: 218 of nursing students experienced stress levels. The average value of stress was 34.59 ± 15.49. The main influential factors on the stress level were somatization and anxiety, followed by induced stress by third parties and workload. There were statistically significant differences in somatization and anxiety between women and men (p<0.05). A statistically significant influence of induced stress by third parties and life events with the academic average (p<0.05) was found. It is necessary to consider new didactic strategies to decrease the induced stress by workload, as well as somatization and anxiety.